Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s13287-022-02977-y
|View full text |Cite|
|
Sign up to set email alerts
|

Stem cells differentiation into insulin-producing cells (IPCs): recent advances and current challenges

Abstract: Type 1 diabetes mellitus (T1D) is a chronic disease characterized by an autoimmune destruction of insulin-producing β-pancreatic cells. Although many advances have been achieved in T1D treatment, current therapy strategies are often unable to maintain perfect control of glycemic levels. Several studies are searching for new and improved methodologies for expansion of β-cell cultures in vitro to increase the supply of these cells for pancreatic islets replacement therapy. A promising approach consists of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 212 publications
0
15
0
1
Order By: Relevance
“…Close spatial proximity of the Schwann cells to the endocrine progenitors suggests that paracrine signalling will be important in influencing differentiation, and further work is required to identify which, if any, of the ligand‐receptor pairs are critical for islet cell development. The lack of an in vitro niche containing the appropriate signalling factors required for full beta cell specification is thought to contribute to the immature cells produced by current stem cell differentiation protocols, 59 , 60 leading to the requirement for an additional in vivo maturation stage. A thorough understanding of the pancreas microenvironment in which the endocrine progenitors mature may, therefore, reveal signalling factors or ligands that can be included in current differentiation cocktails to increase the maturation of stem cell‐derived beta cells in vitro.…”
Section: Pancreatic Microenvironmentmentioning
confidence: 99%
“…Close spatial proximity of the Schwann cells to the endocrine progenitors suggests that paracrine signalling will be important in influencing differentiation, and further work is required to identify which, if any, of the ligand‐receptor pairs are critical for islet cell development. The lack of an in vitro niche containing the appropriate signalling factors required for full beta cell specification is thought to contribute to the immature cells produced by current stem cell differentiation protocols, 59 , 60 leading to the requirement for an additional in vivo maturation stage. A thorough understanding of the pancreas microenvironment in which the endocrine progenitors mature may, therefore, reveal signalling factors or ligands that can be included in current differentiation cocktails to increase the maturation of stem cell‐derived beta cells in vitro.…”
Section: Pancreatic Microenvironmentmentioning
confidence: 99%
“…On page 8 of the original article [ 1 ], in the sentence: "… differentiation of iPSCs in pancreatic β-cells, namely Wnt; Nodal/Activin A; BMPs; FGF; EGF (epidermal growth factor); Hedgehog; retinoid; and Notch (Fig. 1).".…”
Section: Correction To: Stem Cell Research and Therapy (2022) 13:309 ...mentioning
confidence: 99%
“…7 As the technology to develop stem cell-derived beta-cells and islets mature, demand for islet transplantation is expected to increase and the procedure become more widespread. 8 Identification of new and improved methods for pancreatic islets implantation has become an important area of research. 9,10 In an attempt to overcome deficiencies related to the injection of pancreatic islets through the portal vein, while retaining the advantages of islet implantation into the liver, Fujita et al reported on a method of direct transplant of pancreatic islets, in the form of an isletcell-sheet, onto the liver surface.…”
Section: Introductionmentioning
confidence: 99%